“Review Article on Tridax Procurmbens Herbal Antibacterial Cream” - Gaurav Brijlal Sonawane; Neha.P.Patil; Mrunal.D.Pendharkar; Krutadnya.P.Patil; S.P. Pawar; Prashant Ganesh Shimpi (Recent Trends in Cosmetics, 2026)
Abstract Tridax procumbens (L.), also referred to as coat buttons or tridax daisy, is a common plant in the Asteraceae family that is well-known for its exceptional pharmacological and therapeutic properties. This plant has long been utilized as an anticoagulant, antifungal, insect repellent, wound healer, and hepatoprotective agent in Indian Ayurveda. With a focus on its medicinal and formulation features, the current study offers a thorough summary of its botanical traits, phytochemical components, and pharmacological activity. A wide range of biological effects are caused by flavonoids, alkaloids, tannins, carotenoids, glycosides, terpenoids, and saponins, according to phytochemical analysis. T. procumbens has been shown in several studies to have antioxidant, anti-inflammatory, antidiabetic, hepatoprotective, antihypertensive, immunomodulatory, and anticancer effects. Compounds like tridaxin, betaine, oleanolic acid, lupeol, and quercetin, which together add to its therapeutic potential, are principally responsible for these properties. Additionally, the creation of herbal formulations made from T. procumbens extracts, such as antiseptic and wound-healing creams, has demonstrated positive outcomes in terms of stability, spreadability, pH balance, and non-irritability, confirming its appropriateness for topical administration. Tridax procumbens stands out as a remarkable natural resource with enormous promise for future phytopharmaceutical research, fusing ancient wisdom with contemporary scientific confirmation, as public interest in herbal and sustainable therapies continues to grow.
Keywords: Herbal cream; Phytomedicine; Tridax procumbens; Wound Healing; antibacterial activity